Effects of drying strategies on sporulation and titer of microbial ecological agents with Bacillus subtilis - Li, Chonglei; Zhao, Kai; Ma, Litong; Zhao, Ji; Zhao, Zhi-Min (Frontiers in Nutrition, 2022)
Drying operation is beneficial to the preservation and transportation of microbial ecological agents. In this study, drying kinetics and water distribution variations in solid biomass medium during hot air drying (HAD) and vacuum freeze drying (VFD) were systematically investigated. Meanwhile, effects of different drying strategies on sporulation of Bacillus subtilis and the titer of microbial ecological agents were compared. Results showed that both HAD and VFD induced rapid water removal from the solid biomass medium. VFD retained bound water and maintained the porous structure of solid medium. Both HAD and VFD induced sporulation. The expression level of sporulation-regulatory genes spo0A, sigF, and sigE followed the order 80 °C-HAD > 60 °C-HAD > VFD. The spore number in medium after 80 °C-HAD drying for 6 h was 0.72×1010/g dry medium, which was 9.1% and 12.5% larger than that of medium with 60 °C-HAD and VFD, respectively. Therefore, 80 °C-HAD is an effective drying strategy for promoting sporulation, which improves the titer of microbial ecological agents with B. subtilis.